Mobbing of line manager and stress perceived by nursing staff in a public hospital in Huánuco, Peru - Dionicio Acosta, Carmen Flor (2022)
Objective. To determine the correlation between mobbing by line manager and stress among the nursing staff of the Surgical Center and Neonatology Service of the Hospital de Contingencia Hermilio Valdizán Medrano, Huánuco, 2019. Methods. The research had a quantitative approach and was observational, analytical and cross-sectional. The data collection instruments were the Heinz Leymann questionnaire and the Gonzalez de Rivera stress reactivity index (SRI) test, after reliability validation. Spearman's Rho test was applied in the inferential analysis. In addition, ethical aspects were taken into consideration. Results. 82.5 % (52) of the sample showed evidence of mobbing by their respective line managers at a mild level; 74.6 % (47) had a low level of stress. When analyzing the correlation between the variables, mobbing by line managers and nursing staff stress, a moderate correlation was found [(Rho = 0.608), (p = 0.000)]. Conclusions. There is a correlation between line managers mobbing and stress in the nursing staff under study.